Notes on the Nodal and Relative Lateral Stability Bracing Requirements of AISC 360 - Louis F. Geschwindner and Andres Lepage (Engineering Journal, 2013)
The requirements for stability bracing of columns and beams have been included in AISC specifications since 1999. These requirements are intended to permit properly braced columns and beams to attain the buckling strength of the member as if braced by immovable supports and thus be designed as braced members according to the requirements of the Specification. The Specification addresses lateral stability bracing of columns and beams and torsional stability bracing of beams. This paper will address only the requirements for lateral stability bracing. Although these requirements appear to be fairly straightforward, one question is regularly asked by those trying to put them into practice: What is the difference between "nodal"ť and "relative"ť bracing? This paper looks at the background of the provisions, describes how they have been obtained from the theoretical equations and then suggests how best to distinguish between these "nodal"ť and "relative"ť braces. It also shows that the approach taken by the Specification is safe and permits simple rules to be applied to a wide range of bracing problems. In addition, recommendations are made for revision of the requirements.